Genetic relationship and correspondence of Salmonella Typhi isolated from water samples in typhoid outbreak localities with food handlers and contact by using Pulsed Field Gel Electrophoresis (PFGE) - Salwani H.; Mohd Nuramin A.; Fauziah M.N.; Hani M.H.; Wan Mansur H.; Phua K.K.; Asma I.; Aziah I. (2024)
Indexed by SCOPUS